Hydrogen production from ethanol steam reforming on M/CeO2/YSZ (M=Ru, Pd, Ag) nanocomposites - Carbajal Ramos, Ines Alejandra (2012)
M/CeO2/YSZ nanocomposites (M = Ru, Pd, Ag) were prepared by successive impregnation and tested in the ethanol steam reforming (ESR). Ru/CeO2/YSZ demonstrated good activity and stability under reaction conditions. Pd/CeO2/YSZ shows good initial activity but suffers of significant deactivation while the performances of the Ag-based sample were rather poor. A plethora of different structural (Powder XRD), microstructural (HR-TEM), morphological (surface area, CO chemisorption) and thermal analysis characterization techniques were used to evidence the modification of the samples induced by prolonged exposure to the reaction mixture. The promising performances of Ru/CeO2/YSZ were associated to the combination of the positive action of the metal selectivity to syn-gas and of CeO2 in metal dispersion stabilization and coke deactivation prevention.